The Mandira Quilombola Community and the Production of an Anthropophagic Identity - de Matos Gondim, Diego [UNESP]; Miarka, Roger [UNESP] (Springer Nature, 2020)
The following article presents a discussion about the production of the identity of a community of Brazilian African-descendants called Mandira, formed in 1868 and recognized as a Quilombola Community in 2015, currently composed of around a hundred people living in the Vale do Ribeira Region, in southeast of Brazil. The text is based on a finished Master’s Degree research and on a PhD study currently in course that involve a participative fieldwork and cartography as methodology. As a result, the concept of Anthropophagic Identity is created, in which the identity of a community is never static, but always dynamic, with the sense of devouring different elements and circumstances that it goes through.
Keywords: Anthropology; Difference and repetition; Ethnomathematics; Philosophy of difference; Territory